Finding the Right Article Type for Your Scholarly Work in Pharmacy Education - Kristin Janke (University of Minnesota Libraries Publishing, 2018)
Abstract Over the last eight years, a number of new article types have been made available to support scholarship in pharmacy education.  This commentary aims to describe the evolution of the article types and a process for matching the phase of educational scholarship with available types.  Success in publishing requires knowledge of the journals publishing education-related manuscripts, as well as the article types and their specifications.  In order to determine the best fit for your manuscript, authors are encouraged to review each journal's guidelines for the various article types. Creative Commons License: CC BY-NC Disclosures: The author is Executive Associate Editor for Currents in Pharmacy Teaching and Learning and Editor for Innovations in Pharmacy with responsibility for the Education Section. Acknowledgements: The author thanks the Education Team of Innovations in Pharmacy including, Andrea Franks, Pharm.D., Katherine Kelley, Ph.D., Lara Kerwin, Pharm.D. , Claire Kolar, Pharm.D., Ph.D., and Michael Nelson, Ph.D., for their comments on an earlier version of this manuscript. Type: Commentary